Semiotics of the norm: the case of the Mischlinge in Nazi legislation - Bassano, Giuditta (Rivista Italiana di Filosofia del Linguaggio, 2023)
In this contribution, we address a specific aspect of semantic categorisation through the example of a well-known Nazi racial law. We will see how the Nazi law aimed to construct the identity of Jewish people by separating them from Aryan people. In doing so, it created a threshold between Aryans and Jews, where it placed people defined as Mischlinge. This will first allow us to observe the relationship between semantic categorisation and differentiation. Secondly, we propose that norms can be understood, in a semiotic sense, as processes with rather precise implications. Indeed, we will speak of normative processes because they are generalising, imply territorialisation and the role played by the threshold concept